REMOBILISATION OF THE CONTINENTAL LITHOSPHERE BY A MANTLE PLUME: MAJOR-, TRACE-ELEMENT, AND SR-, ND-, AND PB-ISOTOPE EVIDENCE FROM PICRITIC AND THOLEIITIC LAVAS OF THE NORILSK DISTRICT, SIBERIAN TRAP, RUSSIA - Lightfoot P.C.; Hawkesworth C.J.; Hergt J.; Naldrett A.J.; Gorbachev N.S.; Fedorenko V.A.; Doherty W. (My University, 1993)
The Late Permian to Early Triassic Siberian Traps have been sampled by drill core (core SG-9) and from surface exposure (section 1F) in the Noril'sk region of the Siberian Platform, Russia. Combined major, trace element, and Nd-, Sr-, and Pb-isotope data on selected samples through the Siberia Trap, offer new chemostratigraphic criteria for the identification and characterisation of two fundamentally different magma types and 9 of the 11 formations of lava developed near Noril'sk. A Lower Sequence of sub-alkalic basalts, tholeiites, and picritic basalts (upwards these are the Ivakinsky, Syverminsky, and Gudchichinsky formations) are overlain by an Upper Sequence of picritic basalts and tholeiites interbedded with tuffs (upwards, these are the Khakanchansky, Tuklonsky, Nadezhdinsky, Morongovsky, Mokulaevsky and Kharayelakhsky formations).The Gudchichinsky and Tuklonsky formations contain both picritic and tholeiitic lavas. The Tuklonsky formation tholeiites and picrites have moderate Gd/Yb (1.6–1.8), low TiO2 (0.45–0.95 wt%), a significant negative Ta and Nb anomaly (Nb/La =0.42–0.57) and unradiogenic Nd (ɛ NdCHUR = to -4.6). In contrast, both the Gudchichinsky formation tholeiites and picrites have high Gd/Yb (2.3–3.1), and TiO2 (1.2–2.3 wt%), no significant Nb or Ta anomaly (Nb/La =0.8–1.1), and radiogenic Nd (ɛ NdCHUR = to 7.3). The low-Ti and Nb/La, high La/Sm, and unradiogenic Nd-isotope signatures of the picritic Tuklonsky formation lavas and the tholeiitic lavas of the Upper Sequence are characteristic of magmas strongly influenced by material from the continental lithosphere, whereas the high-Ti and Nb/La, low La/Sm and radiogenic Nd-isotope signatures of the Lower Sequence are more comparable to deeper asthenospheric mantle-plume generated lavas similar to oceanic island basalts. The lavas overlying the Tuklonsky formation have mg-numbers of 0.63 to 0.68, and are more evolved than the Tuklonsky (Mg-number < 0.62) and have more radiogenic ɛ NdCHUR (Tuklonsky:-0.03 to-4.66; Mokulaevsky: + 0.60 to + 1.61), but have many of the incompatible trace element features of the Tuklonsky sky type magma. These lavas show a progressive upwards decline in SiO2 (55–49 wt%), La/Sm (4.6–2.0), and ɛ URSr ( + 67 to + 13) which has previously been attributed to a decrease in the proportion of crustal material contributed to the magma. This paper explores and alternative model where a component of the crustal contribution might be derived from within an ancient region of the mantle lithosphere as recycled sediment rather than from the overlying continental crust.
Keywords: Permian; Triassic; Paleozoic::Permian; Mesozoic::Triassic; Мезозой::Триасовая; Палеозой::Пермская